Peran Guru Terhadap Perkembangan Peserta Didik Dalam Proses Pembelajaran Sekolah TKQ Masjid Muslimin - Yella Firliana Sinaga; Riska Khairani Sinaga; Namirotul Arofat Lubis; Saafira Najwa An-Nada; Rafli Pasha; Maulana Hakim (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
Based on research and observations that have been carried out at TKQ Muslimin Mosque (jln Turi/jln H. Bahrun Jamil, SH No.20- Medan) it can be concluded that teachers have a very important role in the development process of students in the learning process. Where, teachers- Teachers have a very important role in guiding children at school by teaching what patience means, the nature of helping each other, being able to create interactions with students, and providing opportunities for students to express the opinions they have received. Being a teacher definitely has challenges or obstacles in the learning process, be it misbehavior by students in class who lack concentration in learning, sleeping in class, etc. Therefore, giving praise as a form of a teacher's attention to his students is very important in forming students' personalities. .The stages in research on the role of teachers in student development are divided into 5 stages, namely: 1) Research context, 2) Participants, 3) Research design, 4) Data collection, 5) Data analysis. The purpose of this research is to find out how important the role of teachers is in the development of students in the learning process. The targets of this research were teachers at the TKQ Mesjid Muslimin school located at (jln Turi/jln H. Bahrun Jamil, SH No.20- Medan).